Effect of Fasciola hepatica proteins on the functioning of rat hepatocytes - Wesołowska, Agnieszka (Springer-Verlag, 2011)
Fasciolosis is a hepatic parasitic infection that affects many mammal species and creates a great economic and veterinary problem. Molecular mechanisms of parasite–hepatocyte interactions have not been precisely characterized yet. Therefore, the aim of the study was to investigate alterations in the metabolic activity of rat liver cells exposed to Fasciola hepatica somatic proteins. Hepatocytes were incubated with 0–1 mg/ml of fluke's somatic proteins for various periods of time. Afterward, changes in hepatocytes metabolic activity were determined with MTT and enzyme leakage tests. Hepatocytes' capacity to synthesize albumin was also investigated. It was observed that protein concentration, as well as longevity of their action, influenced metabolic activity of rat liver cells. Diminution of hepatocytes survival rate, an increase in enzyme leakage and altered synthetic capacity after treatment with parasite's proteins were reported. It is concluded that somatic proteins of F. hepatica may play an important role in liver cell damaging.